Metachronous triple primary neoplasms with primary prostate cancer, lung cancer, and colon cancer: A case report. Issue 26 (June 2018) - Feng, Yuhua; Zhong, Meizuo; Zeng, Shan; Xiao, Desheng; Liu, Yiping
Abstract: Rationale: Multiple primary neoplasms (MPNs) are rare. Most MPNs are double, and triple primary neoplasms are extremely rarer. Here, we describe a case of a 66-year-old man diagnosed with metachronous triple primary neoplasms with primary prostate cancer, lung cancer and colon cancer. Patient concerns: The patient complained of dysuria in January 2015, and he underwent transurethral resection of the prostate. The pathological results showed acinar adenocarcinoma of prostate with a Gleason score of 3+3. In January 2017, he complained of lower abdominal pain, then he took an enteroscopy examination, found a mass in the sigmoid colon, and positron emission tomography/computed tomography examination showed masses in the sigmoid colon and right upper lobe of the lung. Biopsy of the colon showed moderately differentiated adenocarcinoma with Kirsten rat sarcoma viral oncogene homolog exon 2 mutation, and biopsy of the lung showed moderately differentiated adenocarcinoma with epidermal rowth factor receptor exon 21 mutation. Diagnoses: Metachronous triple primary neoplasms with primary prostate cancer, lung cancer and colon cancer. Interventions: The patient underwent surgical resection of the right upper lobe of the lung, postoperative stage was T1bN0M0 (stage IA). After 8 cycles of chemotherapy with modified FOLFOX6 regimen (oxaliplatin 85 mg/m 2, leucovorin 400 mg/m 2, 5-fluorouracil 400 mg/m 2 on day 1, followed by 5-fluorouracil 2400 mg/m 2 intravenous infusion over 46 hours every 2 weeks), the patient underwent radical resection of colon cancer, and he finished the remaining 4 cycles of modified FOLFOX6 regimen chemotherapy in November 2017. Outcomes: The patient takes examination every three months, and the results show no recurrence. Lessons: When considering MPNs, thorough surveillance by new screening methods is required to detect a second or even third neoplasm at an early stage.